2022
DOI: 10.3389/fmed.2021.774623
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1: A Circulating Biomarker for Pulmonary Hypertension Diagnosis Among Chronic Obstructive Pulmonary Disease Patients

Abstract: Pulmonary hypertension (PH) is a common complication of chronic obstructive pulmonary disease (COPD) and induces increased mortality among COPD patients. However, there are no blood biomarkers to identify PH in COPD. Here, we investigated whether circulating angiogenic factors and cytokines could serve as (a) biomarker (s) for COPD-PH patients. Using Angiogenesis and Cytokine proteome profile array assay, we measured the level of 36 cytokines and 55 angiogenesis-associated proteins in plasma from four COPD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…According to a previously described protocol with some modification, CSE was freshly prepared on the day of each experiment and used within half an hour in vitro experiments 24 . In this research, we tested the optical density (OD) values of 100% CSE to partly maintain the stability of CSE concentrations in in vitro experiments 27 . Firstly, one cigarette (Marlboro, Philip Morris, USA) was burned, and the smoke passed through 10 mL of phosphate-buffered saline (PBS) by connecting to a vacuum pump with a constant pressure of -0.1 Kpa.…”
Section: Preparation Of Cse In Vitromentioning
confidence: 99%
“…According to a previously described protocol with some modification, CSE was freshly prepared on the day of each experiment and used within half an hour in vitro experiments 24 . In this research, we tested the optical density (OD) values of 100% CSE to partly maintain the stability of CSE concentrations in in vitro experiments 27 . Firstly, one cigarette (Marlboro, Philip Morris, USA) was burned, and the smoke passed through 10 mL of phosphate-buffered saline (PBS) by connecting to a vacuum pump with a constant pressure of -0.1 Kpa.…”
Section: Preparation Of Cse In Vitromentioning
confidence: 99%
“…Impaired protease–anti-protease imbalance in COPD patients is associated with the presence of airway injury [ 79 , 134 , 135 , 136 , 137 ]. In particular, TIMP-1 has the ability to moderate ECM degradation both in healthy tissues and under pathological conditions [ 40 , 42 , 138 , 139 ]. For example, the presence of circulating TIMP-1 has been shown to control proteolysis in the cardiovascular system [ 140 , 141 ].…”
Section: Timps In Copdmentioning
confidence: 99%
“…Furthermore, TIMP-1 preferentially inhibits MMP-9, a key metalloproteinase in the pathogenesis of emphysema; therefore, TIMP-1 may exert protection, while the levels of MMP-9 and the MMP-9/TIMP-1 ratio are reliable predictors of emphysema [ 142 , 143 ]. On the other hand, TIMP-1 levels were found to be elevated in COPD patients, and plasma TIMP-1 levels were associated with disease severity [ 106 , 135 , 138 ]. Furthermore, TIMP-1 was found to be enhanced in PH, a very common and lethal comorbidity of COPD, compared to COPD patients, suggesting that TIMP-1 levels could be used as a biomarker to identify high-risk patients [ 138 ].…”
Section: Timps In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…TIMP-4 may contribute to extracellular matrix deposition in SSc, and its serum levels have been shown to correlate with systolic pulmonary arterial pressure (sPAP) after echocardiography in both SSc-PAH and PH patients in general [ 63 , 64 ]. Other evidence has shown that serum MMPs levels are also increased in SSc patients with interstitial lung disease (ILD) [ 65 , 66 ], whereas TIMPs appear to be more specifically associated with vascular changes [ 64 , 67 ]; however, no studies to date have compared the serum levels of these molecules between patients with SSc-ILD and SSc-PAH.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%